Multimodal narratives about death in the children’s picture book: typologies and most frequent resources - Hidalgo Rodríguez, Mª Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Current children's picture books that focus on death are studied, considering these publications a fundamental resource to create necessary dialogues with childhood. After analyzing a sample of ten picture books following a qualitative methodology, three typologies are extracted: albums that show the importance of memory for healing after loss, those that focus on the acceptance of death as something nat- ural, and those that claim the memory of ancestors. The predominance of picture books about the relationships between grandchildren and a grandparent who ends up dying, shows the scarcity of other less dramatic perspectives.